The Effect of Cupping Ttherapy on Sleep Quality in Post Stroke Patients - Livia Amelia; Agus Purnama (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2023)
Background: Stroke is the leading cause of disability and the fifth cause of death. In addition to death and disability, it turns out that other effects of stroke disease can experience sleep disturbances and problems, so the quality of sleep becomes poor and can affect the degree of disability in stroke patients, so it is necessary to undergo therapy with various modalities, such as cupping therapy. Objectives: The purpose of this study was to identify the effect of cupping therapy on the sleep quality of post-stroke patients, identify the picture of sleep quality before being bought cupping therapy in post-stroke patients, and identify the picture of sleep quality after being given cupping therapy in post stroke patients. Methods: The research design in this study used a quasi with a pre-test post-test group one design for 2 weeks without any control groups with the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Results: After 2 weeks of treatment, the respondents showed an increase in their ability to sleep, the average quality of sleep before being given intelligence, namely 9.200, and the average value of cells that were given intelligence, namely 3.733. The results of the effect test obtained a p-value <0.001 and the result of the effect size was 3.42 and it was obtained It was concluded that there was a significant difference between sleep quality before intelligence was given and sleep quality after intelligence was given. Conclusion: A complementary therapy that can be used for stroke is cupping therapy. stroke sufferers can experience sleep disturbances so that the quality of sleep becomes poor and affects the degree of disability. then there is a takeover, the impact is that it can cause drowsiness and deep sleep.